1980
DOI: 10.1097/00000658-198003000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Intravascular Coagulation and Portal Hypertension Following Pancreatic Islet Autotransplantation

Abstract: A patient undergoing subtotal pancreatectomy and intraportal islet tissue autotransplantation for chronic pancreatitis developed severe portal hypertension (49 cm of H(2)O) and acute disseminated intravascular coagulation (DIC). In an attempt to identify the cause of these problems, portal pressure and the activities of the coagulation and fibrinolytic systems were studied in dogs undergoing intraportal autotransplantation of islet tissue. Following intraportal injection of the pancreatic tissue in five contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0
1

Year Published

1981
1981
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(51 citation statements)
references
References 6 publications
2
48
0
1
Order By: Relevance
“…They demonstrated that total islet yields with no purification in both groups were similar, and that the percentage of embedded islets was significantly higher in the NB1 group compared to the Liberase group. The purification procedure is not always necessary for auto-islet transplantation unless the volume of whole islet preparation is high, which may increase the risk of intrahepatic thrombo-embolic events (31). However, in allogeneic islet transplantation, the purification process is a key for successful islet isolation and to reduce the volume of antigenic tissue implanted into the recipients.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that total islet yields with no purification in both groups were similar, and that the percentage of embedded islets was significantly higher in the NB1 group compared to the Liberase group. The purification procedure is not always necessary for auto-islet transplantation unless the volume of whole islet preparation is high, which may increase the risk of intrahepatic thrombo-embolic events (31). However, in allogeneic islet transplantation, the purification process is a key for successful islet isolation and to reduce the volume of antigenic tissue implanted into the recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Shortly after the initial report on IAT from the UMN more than 30 years ago (Sutherland et al, 1978), a few other centers also did IAT after total or partial pancreatectomy (Cameron et al, 1981;Fontana et al, 1994;Hinshaw et al, 2011;Mehigan et al, 1980;Mehigan et al, 1980;Memsic et al, 1984;Mirkovitch et al, 1981;Toledo-Pereyra et al, 1984;Traverso et al,1981) though because they were done without anticoagulation complications of the IAT occurred at some centers (Mehigan et al, 1980;Memsic et al, 1984;Toledo-Pereyra et al, 1984), but inexplicably not at others (Fontana et al, 1994;Hinshaw et al, 2011;Valente et al, 1986). Later several center began programs with low complication rates because of lessons learned from the others (Blondet et al, 2007).…”
Section: Historical Contextmentioning
confidence: 99%
“…Dogs are particularly susceptible to the development of portal hypertension, and Kretschmer et al [183] found transplantation by this route not to be as effective as transplantation to the spleen. Mehigan et al [ 184] described disseminated intravascular coagulation and portal hypertension after intraportal transplantation. This syndrome was secondary to tissue thromboplastin in the preparation and could be prevented by prophylatic administration of heparin and aprotinin.…”
Section: Dispersed Adult Pancreas Without Islet Purificationmentioning
confidence: 99%